Impact of initial imaging with gallium‐68 dotatate PET/CT on diagnosis and management of patients with neuroendocrine tumors. Issue 3 (18th December 2019) - Crown, Angelena; Rocha, Flavio G.; Raghu, Preethi; Lin, Bruce; Funk, Gayle; Alseidi, Adnan; Hubka, Misho; Rosales, Joseph; Lee, Marie; Kennecke, Hagen
Abstract: Background: Somatostatin analog functional imaging with gallium‐68 (Ga‐68) dotatate positron emission tomography/computed tomography (PET/CT) has demonstrated superiority in lesion detection in patients with neuroendocrine tumors (NETs). The clinical impact of this imaging modality on US surgical and medical oncology practices has not been established. Methods: Consecutive patients with NET at our institution who received an initial Ga‐68 dotatate PET/CT between July 2017 and September 2018 were included. Ga‐68 dotatate PET/CT was compared with prior imaging. Results: Among 101 eligible patients, 51 of 50 were female/male, site of origin was gastroenteropancreatic (75%), unknown primary (13%), lung (8%), thymus (2%), and other (2%). All NETs were histologically well/moderately differentiated. Ga‐68 dotatate imaging findings altered management in 36 (35.6%) patients: documentation of progression led to the initiation of systemic therapy in 14 patients, obviated the need for biopsy in four patients, and altered surgical plans in 7 of 14 (50%) patients referred for surgery. In 11 patients, decisions regarding peptide receptor radionucleotide therapy and somatostatin analogs were altered. Conclusions: In this series, Ga‐68 dotatate PET/CT altered diagnosis and management in one‐third of patients and changed operative plans in half of the patients who were referred for surgical evaluation. These results support the routine use of this imaging in the care of patients with early‐stage and advanced NETs.